ARTIFICIAL INTELLIGENCE IN CHEMISTRY EDUCATION: OPPORTUNITIES, ETHICAL CHALLENGES, AND THE DEVELOPMENT OF CRITICAL THINKING IN SECONDARY AND VOCATIONAL SETTINGS - Xafiza Rustamova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
The rapid integration of artificial intelligence (AI) tools is transforming chemistry education at secondary and vocational levels. This review synthesizes recent empirical studies and systematic reviews (primarily 2023–2025) on AI applications in chemistry teaching, including large language model (LLM) chatbots, adaptive learning platforms, and virtual laboratory simulations. Using the UNESCO Recommendation on the Ethics of Artificial Intelligence (2021) as the primary normative framework, the article examines the demonstrated benefits of AI—personalized feedback, enhanced molecular visualization, improved student self-efficacy, and scalable differentiated instruction—alongside persistent limitations, including computational errors in stoichiometric and redox calculations (with reported mechanistic accuracy as low as 28% for early models), hallucinated citations, and algorithmic bias. Six concrete ethical dilemmas specific to chemistry education are analyzed through detailed scenarios: data privacy and learner profiling, academic integrity in AI-assisted laboratory reports, algorithmic bias in automated assessment, the virtual–real competency gap in vocational training, the opacity of AI-driven assessment decisions, and digital inequality. The article argues that AI’s pedagogical effectiveness is inseparable from its capacity to foster critical thinking in both students and educators. A practical four-pillar framework for responsible implementation is proposed, with implications for curriculum design, teacher professional development, and institutional policy. Directions for future empirical research in secondary and vocational contexts, particularly in resource-constrained settings, are identified.